Cover cropping increased phosphorus stocks in surface sandy Ultisols under long‐term conservation and conventional tillage. (29th April 2020) - Ye, Rongzhong; Parajuli, Binaya; Ducey, Thomas F.; Novak, Jeffrey M.; Bauer, Phil J.; Szogi, Ariel A.
Abstract: Low use‐efficiency and high environmental significance of phosphorus (P) requires a better understanding of its stocks and behavior in soils. We investigated P fractions in sandy Coastal Plain Ultisols, where long‐term conservation agriculture driven by conservation tillage and residue return for ∼40 yr and the integration of cover cropping for 4 yr has been demonstrated to improve soil organic matter. Soils were collected from fields at 0‐ to 5‐ and 5‐ to 15‐cm depths to study the effects of tillage (conservation vs. conventional) and cover crop (with vs. without) on soil stocks of various chemically defined P pools and the phosphatase potential activities. Conservation tillage increased KCl‐extractable inorganic P (KCl‐Pi) stocks in top soils (0–5 cm) when compared to conventional tillage, but had no effects on other pools at both soil depths. Cover cropping caused significant accumulations of NaOH‐extractable organic P (NaOH‐Po) in top soils (0–5 cm). Nonetheless, neither conservation tillage nor cover crop changed the contributions of the chemically defined pools to soil total P with NaOH‐Po dominating at both soil depths followed by NaOH‐extractable inorganic P (NaOH‐Pi) and HCl‐extractable Pi (HCl‐Pi). Conservation tillage increased phosphatase potential activities by 128% in the 0‐ to 5‐cm soils, whereas no cover crop effects were observed. Conservation tillage improved P availability potentially through its effects on microbial activities, whereas cover cropping increased P stocks and availability by promoting Po accumulations.